Anesthetic Considerations in Patients with Mitochondrial Disorders - Maritska, Ziske; Parisa, Nita; Karina, Mathius; Putra, Marco Manza; Eliska, Noviyanti; Irga, Muhammad; Manurung, Maya Rina Santara; Saputra, Andre (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Mitochondrial Disorders (1/4,000 patients) are rare and caused by dysfunctional mitochondria. Anesthetic consideration in patients with Mitochondrial Disorders involves careful preoperative and perioperative observations. Objective: To provide a brief insight into how general anesthetics interfere with mitochondrial energy formation pathways and help form precautions for anesthesiologists when managing patients with Mitochondrial Disorder. Review: Mitochondrial Disorder patients would experience various health problems, such as damaged cardiac functions, neurology systems, and musculoskeletal functions due to energy production disruptions by dysfunctional mitochondrial processes. Moreover, patients with Mitochondrial Disorders exhibit hyperreactivity to volatile anesthetics. Conclusion: No anesthetic strategies are found to be safe in patients with Mitochondrial Disorder yet. Therefore, anesthesiologists should remain alert when monitoring fluid choices and managing patient temperature with Mitochondrial Disorders.